Reductant‐Induced Free Radical Fluoroalkylation of Nitrogen Heterocycles and Innate Aromatic Amino Acid Residues in Peptides and Proteins. Issue 69 (30th October 2019) - Rahimidashaghoul, Kheironnesae; Klimánková, Iveta; Hubálek, Martin; Korecký, Michal; Chvojka, Matúš; Pokorný, Daniel; Matoušek, Václav; Fojtík, Lukáš; Kavan, Daniel; Kukačka, Zdeněk; Novák, Petr; Beier, Petr
Abstract: A series of fluoroalkylated cyclic λ 3 ‐iodanes and their hydrochloride salts was prepared and used in a combination with sodium ascorbate in buffer or aqueous methanol mixtures for radical fluoroalkylation of a range of substituted indoles, pyrroles, tryptophan or its derivatives, and Trp residues in peptides. As demonstrated on several peptides, the aromatic amino acid residues of Trp, Tyr, Phe, and His are targeted with high selectivity to Trp. The functionalization method is biocompatible, mild, rapid, and transition‐metal‐free. The proteins myoglobin, ubiquitin, and human carbonic anhydrase I were also successfully functionalized. Abstract : Highly selective : The sodium ascorbate‐induced radical fluoroalkylation of indoles, pyrroles, and aromatic amino acids in peptides and proteins by using cyclic hypervalent iodine reagents is reported.